Causes and Efforts to Counter a Crime - Muh. Firmansyah Isa (Universitas Negeri Gorontalo, 2022)
This study aims to determine the causes and countermeasures against a crime. The method used in this study, namely the research methodology used, is empirical research and uses a descriptive qualitative approach and qualitative analysis techniques. The results of this study show that the causes and efforts to overcome a crime there are several causes of the crime that occurs due to the talent of the perpetrator, the environment, the spiritual, and the economy. Crimes range from mild to the most serious forms such as severe mistreatment that cause severe injuries to their victims so that physical and non-physical problems arise. But it is also necessary to realize that, the person who committed the crime is a person like us. Crimes or criminal acts must be dealt with because they create discomfort and insecurity in people's lives, so they can do rational ways of dealing with them. Meanwhile, efforts made to tackle the crime include penal efforts and repressive efforts.